KIDNEY LESIONS IN HIV-INFECTED PATIENTS - М. О. Andrushchak (International Journal of Medicine and Medical Research, 2019)
Introduction. HIV prevalence is one of the most important issues of contemporary medicine. Over a 30-year history of this disease more than 75 million people have been infected with HIV, nearly 30 million adults and children of died. In the future decades, its significance in world premature mortality rates continues to rise. The objective of the study was to establish clinical and laboratory features of kidney lesions in HIV infection.